Dissemination of entrepreneurial opportunities: Processing tempe gembus as nuggets - Sinta Ratna Dewi; Rismayanti Rismayanti; Setia Zuriantini Damai; Eka Septiana Rahayu; Lidya Handoko Saputri (Community Empowerment, 2023)
Tempe gembus (menjes) is a food made from tofu pulp through a fermentation process. Tempe gembus contains nutrients that are suitable for consumption, including energy, protein, carbohydrates, and fiber fat. So far, the utilization of tempe gembus is only limited to fried foods or side dishes. The purpose of this activity is to increase the utilization of tempe gembus as processed healthy nuggets and increase community knowledge and skills in processing healthy nuggets so as to provide entrepreneurial opportunities for the community. The implementation method is by providing counseling and training. The results of this activity show that there is an increase in public knowledge about the use of processed tempe gembus and increased skills in making nuggets made from tempe gembus which is an entrepreneurial opportunity for the community.